2010
DOI: 10.5123/s2176-62232010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Fauna flebotomínica (Diptera: Psychodidae) da Serra do Tepequém, Município de Amajarí, Estado de Roraima, Brasil

Abstract: Com o objetivo de investigar a presença de vetores de Leishmania e inferir sobre o risco de transmissão de leishmanioses a humanos, foi feito um levantamento de flebotomíneos em área endêmica para leishmaniose tegumentar americana na Serra do Tepequém, localizada no Município de Amajari, Estado de Roraima, Brasil. Os flebotomíneos foram capturados no período de agosto de 2008 a maio de 2009, utilizando-se quatro armadilhas luminosas tipo CDC instaladas a um metro de altura do solo, no interior de floresta prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Regarding E. georgii, its type locality is in the municipality of Oriximiná, state of Pará (RYAN, 1986), but this species was described only in 2002 (FREITAS & BARRETT, 2002) based on specimens that had previously been identified as Evandromyia begonae (Ortiz & Torrez), and because of errors in identification, it may be that its real distribution has been underestimated. This species has already been found in Roraima, Amazonas and Pará, which are all states in the Brazilian Amazon region (FREITAS & BARRETT, 2002;GAMA et al, 2010;RYAN, 1986). The finding of these two species increases the number of sandflies registered in Rondônia: recently, Galardo et al (2015) elevated the number of species in Rondônia to 118 and, with our findings, this number is updated to 120 species.…”
Section: Discussionmentioning
confidence: 88%
“…Regarding E. georgii, its type locality is in the municipality of Oriximiná, state of Pará (RYAN, 1986), but this species was described only in 2002 (FREITAS & BARRETT, 2002) based on specimens that had previously been identified as Evandromyia begonae (Ortiz & Torrez), and because of errors in identification, it may be that its real distribution has been underestimated. This species has already been found in Roraima, Amazonas and Pará, which are all states in the Brazilian Amazon region (FREITAS & BARRETT, 2002;GAMA et al, 2010;RYAN, 1986). The finding of these two species increases the number of sandflies registered in Rondônia: recently, Galardo et al (2015) elevated the number of species in Rondônia to 118 and, with our findings, this number is updated to 120 species.…”
Section: Discussionmentioning
confidence: 88%
“…This scenario poses challenges to implement measures recommended by the Brazilian Ministry of Health for the control of CL and is further complicated by the multiple ethnic, cultural and environmental factors that characterize this region [ 4 , 5 ]. Previous studies have shown that Brazil’s Amazon region has undergone profound environmental changes resulting from mining, agriculture and livestock expansion [ 6 ], which may be contributing to changes and maintenance of the leishmaniasis cycle in the area. The State of Roraima, which is in this region, has experienced these changes with an increase of leishmaniasis cases between 2011 to 2015 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%